STRATEGI PENGEMBANGAN KAWASAN WISATA TAKABONERATE DI KABUPATEN KEPULAUAN SELAYAR - Zaenal Akhmad; Ambo Tuwo; Ria Wikantari (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2015)
Takabonerate region has great potential, but there are still many obstacles faced in developing the region. This study aims to determine the priority development strategy in the Takabonerate Selayar. The research method is survey. The approach in this research is qualitative and quantitative approaches to describe the responses of respondents toward tourists and the local community based on questionnaires given object. The obtained data were processed and analyzed using IFAS-EFAS analysis and SWOT. According to the research, based on SWOT Strategy priority is SO Strategies (Strength-Opportunity), a strategy using the strengths and opportunities, while the strategy is Optimizing the management of nature tourism, marine tourism and cultural tourism in the area, improve the coordination with local governments and parties Related to gain support in the development of the region and addressing harassment / threats to the security of the region and build a functional system combined with community elements.